The Effect of Transfer Pricing, Earning Management, CSR and Firm Size in Tax Avoidance - Mukarramah, Makkatul; Nugroho, Lucky (LifeSciFi, 2025)
This study aims to analyze the effect of Transfer Pricing, Earning Management and Corporate Social Responsibility on Tax Avoidance with Firm Size as a Moderating Variable. This quantitative study uses secondary data obtained and can be accessed through the Indonesia Stock Exchange website. The sample for this study consisted of 62 manufacturing companies. This study uses purposive sampling to select the desired sample. The analysis method of this study uses linear regression analysis and moderated regression analysis as analysis tools in Eviews. The study reveals that Transfer Pricing, Earning Management, and Corporate Social Responsibility significantly influence Tax Avoidance in manufacturing firms during 2018–2022. Firm Size strengthens the impact of Transfer Pricing and Corporate Social Responsibility on Tax Avoidance, acting as a moderating factor. However, it does not moderate the relationship between Earning Management and Tax Avoidance. This indicates that Firm Size plays a selective role in amplifying the effects of certain factors on Tax Avoidance but is ineffective in influencing others. These findings highlight the complexity of tax avoidance mechanisms and the varied roles played by organizational characteristics like Firm Size.